Numb chin syndrome as a primary presentation of metastatic breast cancer - Jasjot Sahni; Allan Jones; Glenn Clark; Parish Sedghizadeh (Wolters Kluwer Medknow Publications, 2017)
Numb chin syndrome (NCS) is characterized by facial neuropathy along the distribution of the mental branch of the trigeminal nerve. We report a case of NCS in a 65 year old woman who initially presented to her dentist with nonspecific symptoms that she thought were related to a tooth infection. The patient was otherwise healthy and her medical history was significant for breast cancer treated 20 years prior; her cancer was thought to be in complete remission. Upon clinical examination and conventional dental radiography, no pathology was seen such as odontogenic, periodontal, or jawbone infection. Only paresthesia and hypoesthesia was noted unilaterally in her left chin, jaw and lower lip. A computed tomography scan was obtained for further evaluation and revealed lytic metastatic disease involving the right mandible at the level of the mandibular foramen; lytic lesions of the thoracic vertebrae and multiple pulmonary nodules were also noted. Oncologic referral was made immediately which confirmed a diagnosis of metastatic breast cancer. Familiarity with NCS is important for oral health care providers in order to identify etiology and differential diagnosis, as well as to provide appropriate referral and management.